Implementation of Green Accounting and Community-Based Tourism in Supporting Sustainable Tourism: A Study on Toronipa Beach - Putriana Aksa; Nur Asni; Muntu Abdullah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines the implementation of green accounting and community- based tourism (CBT) as two integrated approaches to supporting sustainable tourism, with a case study at Toronipa Beach, Southeast Sulawesi. The study employs a descriptive qualitative approach based on secondary data, using the Systematic Literature Review (SLR) method and document-based case study. Data were sourced from journals indexed in Scopus and Sinta, official government reports, and publications from international bodies such as UNWTO and UNEP. The findings indicate that: (1) green accounting provides a framework for reporting environmental costs and benefits that remains underutilized in the coastal tourism sector; (2) CBT effectively improves local welfare and ecosystem conservation when supported by strong institutional frameworks; (3) Toronipa Beach has significant potential for applying both approaches synergistically, although it faces challenges in institutional capacity and environmental financial governance; and (4) the integration of green accounting and CBT yields a more comprehensive sustainable tourism model than applying each separately. This research contributes to developing a conceptual model of sustainability-based environmental accounting for coastal tourism destinations in Indonesia.